Barriers and Facilitators for Mental Health Service Use Among Racial/Ethnic Minority Adolescents: A Systematic Review of Literature - Lu, Wenhua; Todhunter-Reid, Abigail; Mitsdarffer, Mary Louise; Muñoz-Laboy, Miguel; Yoon, Anderson Sungmin; Xu, Lei (Frontiers in Public Health, 2021)
Introduction: Mental disorders represent serious public health concerns in the U.S. Compared with Whites, racial/ethnic minority adolescents are more likely to be affected by mental disorders but less likely to use mental health services. This systematic review aimed to summarize factors related to mental health service use among minority adolescents in the U.S. as identified in previous research. Methodology: Following the PRISMA guideline, we systematically searched seven databases for peer reviewed articles related to barriers and facilitators of mental health service use among racial/ethnic minority adolescents. Results: Thirty-two quantitative studies met our inclusion criteria, among which 12 studies (37.5%) sampled mostly Blacks or African Americans, 6 studies (18.7%) focused primarily on Hispanics or Latin/a/x, including Mexican Americans and Puerto Ricans, and 4 studies (12.5%) were mostly Asian Americans (e.g., Chinese, Vietnamese). Based on the socio-ecological framework, 21 studies (65.6%) identified adolescent-related barriers and facilitators of mental health service use, including biological (e.g., age, gender), clinical (e.g., symptom severity), behavioral (e.g., drug/alcohol use), and psychological characteristics (e.g., internal asset) of minority youth. Ten studies (31.3%) identified parents-related factors that influenced minority adolescent mental health service use, including parental perceptions and beliefs, family and parenting issues, and demographic characteristics. Primary factors at the therapist level included ethnic match between patient and practitioner, relationship with healthcare practitioners, and patient-therapist co-endorsement of etiological beliefs. Fifteen studies (46.9%) identified factors influencing minority adolescent mental health service use at the contextual/structural level, including household income, insurance status, and family structure. Lastly, acculturation and school experiences were major factors at the social/cultural level that influence minority adolescent service use. Conclusion: More empirical studies are needed to understand the mechanism underlying minority adolescents' unmet mental health service needs. Culturally competent interventions are warranted to engage minority adolescents with mental disorders into treatment.